Factors Causing the Change of Sustainable Food Agricultural Land to Non-Agricultural in Ogan Ilir Regency - Eko Saputro; Teguh Endaryanto; Dwi Haryono (Journal of Social Research, 2025)
Rapid urbanization and infrastructure development, notably the Trans-Sumatra Toll Road, have intensified the conversion of sustainable food agricultural land (LP2B) to non-agricultural uses in Pemouthan sub-district, Ogan Ilir Regency, threatening regional food security. This study analyzes the interplay of economic, technical, and policy factors driving LP2B changes and evaluates their relative impacts. Quantitative methods were employed, including cluster sampling (92 farmers), high-resolution satellite imagery (2020–2025), and path analysis to model causal relationships. Economic factors (low income, high land value) were most influential (34%), followed by technical (irrigation, machinery; 19.8%) and policy factors (toll roads, spatial planning; 17.5%). Statistical tests (t-test, F-test) and a high determination coefficient (R²=93.6%) confirmed these variables’ significance. The study calls for targeted policies to enhance farmers’ income, improve agricultural infrastructure, and enforce spatial regulations. Future research should explore socio-cultural dynamics and climate adaptation strategies to bolster land preservation.